Validação do método famacha© para o controle das endoparasitoses gastrintestinais em ovelhas da raça morada nova - Ferreira, Josiel Borges (Universidade Federal Rural do Semi-Árido, 2021)
The Morada Nova breed is an important genetic resource in the Brazilian semi-arid region, which currently suffers from problems related to the management of its population and the health management of flocks, increasing the mortality and morbidity rates of these animals. The aim of this study was to validate the FAMACHA© (F©) method for gastrointestinal endoparasitoses control of the Morada Nova ewes. One hundred and thirty-eight adult females were evaluated in the months of March, June, September and December for performance, parasitological, hematological and serum biochemical parameters. The thesis was divided into two chapters, the first evaluating the sensitivity and specificity of the F© system and the second chapter evaluating the agreement between the F© and the packed cell volume (HTC) values under a multivariate approach, using principal component analysis and canonical discriminant. The study concluded that the F© system can be used as a reliable alternative, helping to reduce the selection pressure of anthelmintics in relation to routine selective treatment, for the control of hematophagous parasites and that the relationship between the system categories F© and the HTC bands are similar to the reality of use proposed by VAN WYK and BATH (2002), although they have patterns of particular pathophysiological indicators
Keywords: Análise multivariada; Especificidade; Haemonchus contortus; Raças nativas; Sensibilidade; Multivariate analysis; Specificity; Haemonchus contortus; Native breed; Sensitivity; CIENCIAS AGRARIAS::MEDICINA VETERINARIA